Community imagination as a social process : the case of a protestant church community. - Ong, Yan Sen. (2012)
This article reanalyzes the dynamics of imagination in Benedict Anderson's framework on imagined communities. Past treatments of community imagination are found to be premised on a binary dynamic of existent/non-existent. This article studies ideological schemata and imagination management in a Protestant church community to structure a process-oriented framework that recognizes imagination as a field of heterogeneity and volatility. It ultimately argues for viewing imagination as a social process. This has significant implications for community integrity as well as potential as a practical model for future research and application.